Influence of heat shock and osmotic stresses on the growth and viability of Candida shehatae var shehatae and explore its probiotic potentiality - Promee, Jannatul Sumaiya (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.